Evaluasi Kecepatan dan Keamanan Jaringan Wifi 6 Untuk Konektivitas Masa Depan - Mulyana, Nana; Toni Saidun Ali; Putri Annisa Kalsum (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
WiFi 6 (802.11ax) represents the latest generation of wireless network technology, offering advancements in speed, efficiency, and security. This study aims to evaluate the performance of WiFi 6 in the context of future connectivity, specifically regarding data transfer speeds and protection against cyber security threats. Utilizing a Research and Development approach, this research delivers an implementation model and a technology-based WiFi 6 monitoring system prototype. The results indicate that WiFi 6 demonstrates significant effectiveness in improving network quality, yet continues to face certain security barriers. Solutions based on adaptive encryption systems and real-time monitoring are proposed as novel innovations. Furthermore, the findings show that WiFi 6 can increase speeds by up to 40% and provide enhanced protection through WPA3. This study presents a novel contribution to mapping the positive impacts of WiFi 6 for future connectivity, particularly in meeting the demands of IoT devices and high-density user environments.